A Stylistic Analysis of Lexical and Syntactic in James Clear’s Atomic Habits - Alinmart Paotonan; Murni Mahmud; Auliyanti Sahril Nurfadhilah (General English Education, 2026)
Effective communication in self-help literature relies heavily on clarity, accessibility, and reader engagement, especially when complex behavioral concepts are presented to a general audience. Despite the widespread popularity of Atomic Habits by James Clear, limited research has examined how specific stylistic features contribute to its readability and effectiveness, creating a gap between theoretical discussions of stylistics and practical writing strategies in self-help texts. To address this gap, a stylistic analysis is conducted to explore the lexical and syntactic choices that enhance readability and accessibility, as well as the sentence structures that maintain clarity and reader engagement. A qualitative descriptive method is employed, with data drawn from selected excerpts focusing on vocabulary patterns and sentence construction. The findings reveal that the consistent use of simple, repetitive vocabulary, direct second-person address, short sentence structures, and a dominant active voice significantly improves accessibility. The use of parallel structures and clear information flow supports comprehension and strengthens reader engagement. These findings indicate that effective self-help writing depends on strategic linguistic choices that prioritize simplicity, structure, and reader-oriented communication, enabling complex ideas to be conveyed clearly and persuasively to a wide audience.